Thermo-mechanical analysis of strength degradation of 30SiMn2MoVA gun barrel material during continuous shooting. (September 2022) - Chen, Junyu; Wang, Weijie; Jin, Pengfei; Dou, Caihong; Zhao, Chao; Li, Qiang; Zhang, Cheng; Huang, Jinfeng
Highlights: Exploring the correlations between the mechanical properties and the failure of gun barrel during continuous shooting. The temperature exceeds 700 ℃ at 180 rounds, where the gun barrel is severe softening, this is due to the recrystallization of lath and the growth of cementite. The strength of gun barrel steel at 700 °C is suggested as a key parameter for the development of the long–life gun barrels. Abstract: The internal bore of a machine gun barrel is subjected to the complex effects of cyclic high-temperature and mechanical loadings during the continuous shooting process, resulting in the accumulation of bore damages and eventually the end of the lifespan. The correlation between the ballistic performances and the material properties is a critical issue for the development of gun barrels with a long lifespan. However, it is still not fully understood yet. In this study, the thermo-mechanical analysis of the strength degradation of 30SiMn2MoVA gun barrel steel during continuous shooting is investigated. Irregular rifling deformation of the failed machine gun barrel with a 12.7 mm caliber was observed. Mechanical tensile tests revealed that severe softening occurs in the 30SiMn2MoVA steel when the temperature exceeded 600 °C, where the yield strength decreased significantly from 862 MPa at room temperature to 114 MPa at 700 °C. Transmission electron microscope observations further revealed that the recrystallization of martensitic lath and the growth of cementite softened the gun barrel steel. Moreover, the finite element models are established using the Abaqus software for the evolution of the temperature and stress of the internal wall within 180 cycles. This shows that the peak temperature increases to 730–740 °C and the peak total stress exceeds 246 MPa during 170–180 cycles, which is much higher than the yield strength of 30SiMn2MoVA gun barrel steel. Therefore, the strength of gun barrel steel at 700 °C can be suggested as the key parameter for the development of long-life gun barrels for continuous shooting.